Boundary layer processes impacting the surface energy balance in the Arctic - Maillard, Julia (CCSD, 2022)
The Arctic is warming at two to three times as fast as the rest of the Earth, and it is therefore a crucial area of study for atmospheric scientists. This thesis aimed to gain insight on two characteristics of the Arctic boundary-layer (clouds and surface based temperature inversions) and to determine their impact on the surface energy balance through a combination of novel measurements and modelling. First, a novel statistic of cloud frequency and characteristics over the Arctic sea-ice was derived from a set of 1777 lidar profiles obtained during the 5-year Ice, Atmosphere, Ocean Observation Systems (IAOOS) campaign. Clouds were found to occur more than 85% of the time from May to October and single cloud layers were optically and geometrically thickest in October. Total cloud radiative forcing over a typical summer cycle was estimated to be negative for optically thin clouds, but positive for optically thick clouds. Second, the impact of wind speeds on the development of surface-based temperature inversions (SBIs) in the continental Arctic was investigated. The analysis of measurements from the pre-ALPACA winter 2019 campaign that took place in Fairbanks, Alaska, showed that a local, likely topographically driven flow developed under anticyclonic conditions. This flow inhibited the development of strong SBIs by sustaining significant turbulence even under very strong radiative cooling. The modelling of clear-sky surface layer temperature inversions and their dependence on wind speed was then studied, with a focus on forest areas. A 2-layer analytical model of the vegetated surface layer was developed. This model exhibited a slower decrease of the SBI strength with wind speed compared to a 1-layer model, which was shown to be coherent with observations at an Ameriflux site close to Fairbanks. These models were then compared to two WRF surface layer schemes, which were found to place excessive limits on the turbulence, preventing the development of large temperature gradients. L'Arctique se réchauffe deux à ...